Analisis Faktor Risiko kadar debu Organik di udara terhadap Gangguan fungsi Paru pada Pekerja Industri Penggilingan Padi di Demak - Nugraheni S., F. S.; Joko, Tri; Setiani, Onny (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Background: Industry will not only increase the prosperity of society, but also could bring on an effect of pollution, included rice mill industry at Demak Regency. The effect is air pollution, in which it would take along a disturbance on lung’s function of, especially, workers of the industry. The aim of this research is to find out risk factor of dust’s amount on air at working area to lung’s function of the workers inside, and also to measure the prevalence ratio of dust exposure’s effect to the disturbance of lung’s function on workers. Disturbance of lung’s function, on this research, is limited on lung function parameter, which are FVC, FEV1 and FEV1/FVC ratio and all are classified as dichotomy. Methods: This research is classified as survey analitic research with cross sectional approach. The population is workers on industry at Demak Regency. Research is carried on by measuring lung’s function parameter using Spirometer. The samples are 45 peoples of 3 (three) rice mill industry. They are taken by Simple Random Sampling method of 85 existing workers. Results: The result shows that 34 of 45 respondents are working indoor with the amount of dust is bigger than Limiting Value. From the Statistical Test, we get that the incidence of disturbance of lung’s function on workers is influenced by the amount of dust on air at working area (p value = 0,002), and also strengthened by working duration (p value = 0,000), smoking habit (p value = 0,001), and the existence of history of lung disease (p value = 0,001). The prevalence ratios of each independent variables to the incidence of disturbance of lung’s function are : the amoung of organic dust on air (PR = 3,018, p value = 0.039), and also strengthened by the existence of history of lung disease (PR = 3.535, p value = 0.021), working duration (PR = 4.130, p value = 0.024). Meanwhile, the utilization of masker is proven not influencing in decreasing the incidence of disturbance of lung’s function. It is caused by the utilization on observation is not the real one during the working duration of respondents. Conclusions: Based on the results explained above, we need to implement some exact steps in order to decrease work diseases, which are caused by organic dust of the grain’s grinding, in form of monitoring and controlling held by the industrialists and related institutions to the amount of dust, safety aid (masker) and the workers’ healthy by doing a continue examination of lung’s function Keyword : Organic dust, Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1), FEV1/FVC, Rice mill industry.